Pianificazione ambientale ed emergenza economica negli scenari della globalizzazione - DOI: 10.5752/P.2316-1752.2009v16n18/19p159 - Corlaita, Alberto (Cadernos de Arquitetura e Urbanismo, 2010)
Abstract This paper focuses on some aspects of social and cultural changes taking place in Europe and all over the world in order to develop some considerations about transformations to be introduced in the government of cities and urban areas by town planning, due to huge innovations in economy and finance. Globalization is likely to go on, for a long time, bringing confusion to the mechanisms of town and land use planning. Should the current trends in business persist, they might reproduce ancient liberties, lost not so long ago at a time dominated by the bureaucratic particularism of local laws. Above all, they might affect deeply the troubled relations between production, economic system and environmental frameworks. Key words : Globalization; Environmental planning; Economic systems; Town planning.